1986
DOI: 10.1063/1.336810
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum or phosphorus co-doping effects on the fluorescence and structural properties of neodymium-doped silica glass

Abstract: To utilize the excellent properties of silica (SiO2) glass for a glass laser host, neodymium-aluminum (Nd–Al) and neodymium-phosphorous (Nd–P) co-doped SiO2 glasses were studied. They were prepared by plasma-torch chemical vapor deposition (CVD). It was found that a doping level less than ten times the number of Nd for the Al co-dopant and less than about fifteen times for the P co-dopant was enough to remove undesirable fluorescence properties of Nd-doped SiO2 glasses and make them suitable for laser applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
273
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(280 citation statements)
references
References 22 publications
6
273
1
Order By: Relevance
“…The distortion of the perfect tetrahedral symetry partially lifts the degeneracy of some energy levels such as 3 T 1 ( 3 F) and causes the presence of several peaks assigned to one transition. The Cr(Al) absorption spectrum is similar to those observed in aluminate [7] and alumino-silicate glasses [8] [18,19].…”
Section: Absorption Spectroscopysupporting
confidence: 60%
“…The distortion of the perfect tetrahedral symetry partially lifts the degeneracy of some energy levels such as 3 T 1 ( 3 F) and causes the presence of several peaks assigned to one transition. The Cr(Al) absorption spectrum is similar to those observed in aluminate [7] and alumino-silicate glasses [8] [18,19].…”
Section: Absorption Spectroscopysupporting
confidence: 60%
“…The¸e xp value of the Al-codoped glass is much larger than that of the Al-free glass because of the enhanced dispersion of Nd 3+ ions, resulting in a relatively large¯value (³0.30.4). However, thȩ exp value is not large enough, as compared with PL decay constants reported for NdAl codoped glasses (280450, 3), 4) 257425, 7) 250550, 12) 325, 14) 240250, 17) and 376¯s 27) ). It is partly because of the small z Al /z Nd value (z Al /z Nd = 1).…”
Section: Discussionmentioning
confidence: 82%
“…Most of ), which commonly accelerate the nonradiative transition of PL centers. In Nd-doped silica glasses, PL decay constants as large as ³400 500¯s have been realized by hydrogen-free synthesis using the plasma CVD technique, 4) and by HD isotope exchange of SiOH groups to decrease the phonon energy of the relevant stretching mode.…”
Section: Discussionmentioning
confidence: 99%
“…The reason had remained unclear for a decade. In 1980s, Arai et al 52) measured the density of NdAl-codoped silica glasses, and found that Nd Al codoping brought about a negative volume change on mixing. This result indicated that in some manner, the Nd 3+ ion and the Al 3+ ion are correlated with each other in a silica network.…”
Section: Codoping Of Rare-earth-doped Silica Glass 31 Discovery Of Nmentioning
confidence: 99%